Measurement of intact parathormone after one hour of total thyroidectomy: a predictor of symptomatic hypocalcemia - P., Nabeel T.; Gamalial, Jose; Thomas, Jacob (International Surgery Journal, 2017)
Background: Hypocalcemia is one of the most common complications of thyroidectomy. Hence, parathyroid hormone (PTH) measurement can be used to predict patients at risk for developing significant postoperative hypocalcaemia after thyroidectomy. The present study was conducted with the objective to find out whether there is any correlation between intact PTH value and patients developing symptoms of hypocalcemia after total thyroidectomy and to determine the threshold value of 1 hour post total thyroidectomy (intact PTH level) that can identify those at high risk for developing symptomatic hypocalcemia. Methods: Study involved determination of serum calcium, creatinine and albumin preoperatively, serum intact PTH, 1 hour after completion of total thyroidectomy (i.e. after the closure of skin incision), and serum calcium levels 6, 24 and 48 hours postoperatively. Clinical findings suggestive of hypocalcaemia were also watched for and recorded. Symptomatic signs and/or symptoms were recorded. The patients were followed up for 3 days post operatively and the lowest recorded serum calcium was taken into account. The results were tabulated and entered in Microsoft excel and analysed with spss 17 statistical software. Results: 26% of the study population developed hypocalcemia. Intact PTH was found to be lower in patients who developed symptoms of hypocalcemia. There was a statisticantly significant correlation between the two groups. A one-hour Intact PTH value of 14 pg/ml was found to have high sensitivity (92.3%) and specificity (91.9%). Conclusions: Hypocalcemia is the most common complication after total thyroidectomy. Intact PTH measurement one hour after total thyroidectomy can be used to predict the patients who will develop hypocalcemia after total thyroidectomy. Therefore, patients having low one-hour intact PTH value could be started on calcium supplementation and those having high PTH could be safely discharged early.